Pelatihan Budidaya Hidroponik Dalam Upaya Pemberdayaan Masyarakat dan Kewirausahaan - Kumala Sari, Wahyu; Sinaga, Ego Srivajawaty; Arisandi DN, Dani (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2025)
Biopores come from the word "bio," meaning life, and "pori," meaning pores. Based on the process of their creation, biopores are divided into two types: natural and artificial. Natural biopores are small holes in the soil created by the activities of organisms living in the soil, such as worms, termites, or the movement of plant roots within the ground. Artificial biopores, also known as biopore infiltration holes, are cylindrical holes made vertically into the ground with a diameter of 10-30 cm and a depth of about 100 cm or not exceeding the groundwater level. These holes are then filled with organic waste, which serves to activate soil microorganisms. The objectives of this activity are: to raise awareness within the target community about managing organic waste, to build awareness about the dangers of flooding, to foster a commitment to flood prevention, and to introduce biopore technology as a method of flood prevention. The outcomes of this activity include the target group understanding the relationship between the environment, particularly the connection between waste, floods, and biopores, and agreeing to start managing waste, especially organic waste.